1988
DOI: 10.2527/jas1988.66102668x
|View full text |Cite
|
Sign up to set email alerts
|

Rate, Composition and Efficiency of Growth in Feedlot Steers Reimplanted with Growth Stimulants

Abstract: Eighty Charolais-cross steer calves (283 kg) were fed a moderately high-energy (2.89 Mcal ME/kg) diet for 189 d to examine the effects of reimplantation of 36 mg of zeranol (Ralgro) or 200 mg progesterone plus 20 mg estradiol benzoate (Synovex-S) on the rate, composition and efficiency of gain, skeletal size and carcass parameters in a comparative slaughter trial. The implant treatments included unimplanted controls (C), Ralgro initially (R1), Synovex-S initially (S1), Ralgro initially and a reimplant at 84 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
4
17
2
Order By: Relevance
“…This study confirms that anabolic implants increase mature body size of steers as reported by Preston (1978), Loy et al (1988), and Owens et al (1995) and increase BW at a common grade or body composition (Preston et al, 1990). In agreement with our results, Preston et al (1990) concluded that implanted steers should be harvested at 39.5 kg heavier BW and im-…”
supporting
confidence: 90%
“…This study confirms that anabolic implants increase mature body size of steers as reported by Preston (1978), Loy et al (1988), and Owens et al (1995) and increase BW at a common grade or body composition (Preston et al, 1990). In agreement with our results, Preston et al (1990) concluded that implanted steers should be harvested at 39.5 kg heavier BW and im-…”
supporting
confidence: 90%
“…In our experiment carcass weight of steers was increased similarly to that reported by Apple et al (199 l ) , but our results indicate that the increase in carcass weight of steers was not associated with an increase in longissimus muscle area. In support of our data, Loy et al (1988) reported two implants of Synovex-S increased steer carcass weight 17.9 kg compared with controls but did not alter longissimus muscle area. It is of interest that the response in heifer carcass weight and longissimus muscle area observed in the current trial is more similar to that observed in steers receiving estradiol + progesterone + trenbolone acetate than to that in steers receiving estradiol + progesterone.…”
Section: Resultssupporting
confidence: 90%
“…While in the feedlot (Period 41, implanted calves gained weight at a greater rate ( P c .01) in the first two 28-d periods and tended to gain weight at a greater rate in the third 28-d period ( P = .09) and in the final 40-d period ( P = .12) ( Table 5). Reimplantation with anabolic growth promoters in the feedlot has been effective in increasing calf performance in some studies (Owens et al, 1980;Laudert and Davis, 1983) but has resulted in no additional response in others (Rumsey et al, 1984;Loy et al, 1988). The present data suggest that the response in ADG from implant administered on d 0 of Period 4 had expired by d 56.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…What was of note in the present study was that repeated implants of oestradiol did not cause further decreases in marbling score. This was in contrast to Mader et al (1985) and Loy et al (1988) who reported that repeated implantation with low-potency oestrogenic implants resulted in further decreases in marbling, compared with a single implant. A point of difference may be that in the present study the old implants were removed as new ones were inserted into the ear, which would have resulted in a more constant delivery of oestradiol to the animal compared with programs that simply reimplanted.…”
Section: Discussioncontrasting
confidence: 48%